Colon Cancer Sidedness, Presentation, and Survival at Different Stages. (21st February 2019) - Ulanja, Mark B.; Rishi, Mohit; Beutler, Bryce D.; Sharma, Mokshya; Patterson, Darryll R.; Gullapalli, Nageshwara; Ambika, Santhosh
Abstract : Background . Several prognostic factors have been used to guide therapy for colon cancer (CC). However, the relationship between CC laterality (sidedness) and prognosis remains under investigation. Objectives . To assess the effect of laterality on CC presentation and survival, using a Surveillance, Epidemiology, and End Results (SEER) population-based cohort. Methods . A retrospective cohort study using data from the SEER program (2007-2015). Results . Of the 163, 980 patients with CC, 85, 779 (52.3%) presented with right-sided CC (RCC) and 78, 201 (47.7%) with left-sided CC (LCC). Stage distributions were as follows: stage I, 24.1%; stage II, 27.3%; stage III, 28.2%; and stage IV, 20.4%. In an adjusted modified Poisson regression approach for risk ratio (RR), patients with LCCs were more likely to be male (RR = 1.14; 95% CI 1.12-1.15, p<0.001). As compared to stage I, stage II cancers (RR = 0.88, 95% CI 0.87-0.90, p<0.001) were less likely to be LCC. Stage IV CC was slightly less likely to be left-sided (RR = 0.98, 95% CI 0.98, 0.96-1.00, p = 0.028). The median overall survival (OS) for RCC was 87 months. The median OS for LCC was not established, as more than half of the patients diagnosed with LCC were still living at the time of the analysis. In adjusted Cox proportional Hazard model, individuals with stage I, III, and IV LCCs had superior OS as compared to those with matched-stage RCC (adjusted HR = 0.87; 95% CI 0.85-0.88, p<0.001). However, OS was worse among those with stage II disease who presented with LCC (adjusted Hazard ratio [aHR] = 1.06; 95% CI 1.02-1.11, p = 0.004). CC-specific survival (CSS) was superior for LCC versus RCC for stages III and IV but worse for II. Conclusions . In this population-cohort study, LCC is associated with superior OS and CSS survival. The overall survival advantage was attributed to stage I, III, and IV disease. Individuals presenting with stage II disease exhibit superior survival if the CC is right-sided.